2016
DOI: 10.3390/f7110272
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Forest Thinning Measures for Carbon Budget in a Mixed Pine-Oak Stand of the Qingling Mountains, China: A Case Study

Abstract: Forest thinning is a silviculture treatment for sustainable forest management. It may promote growth of the remaining individuals by decreasing stand density, reducing competition, and increasing light and nutrient availability to increase carbon sequestration in the forest ecosystem. However, the action also increases carbon loss simultaneously by reducing carbon and other nutrient inputs as well as exacerbating soil CO 2 efflux. To achieve a maximum forest carbon budget, the central composite design with two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…The thinning residual removal rate had a larger effect than thinning intensity when considering the ecosystem productivity [34]. Specifically, the lower thinning intensity and higher thinning residual removal rate are beneficial to the ecosystem productivity [35]. This study showed that other stand attributes, including size, density, and species composition, play an important role in determining aboveground carbon content, which is consistent with previous studies [36,37].…”
Section: Discussionsupporting
confidence: 89%
“…The thinning residual removal rate had a larger effect than thinning intensity when considering the ecosystem productivity [34]. Specifically, the lower thinning intensity and higher thinning residual removal rate are beneficial to the ecosystem productivity [35]. This study showed that other stand attributes, including size, density, and species composition, play an important role in determining aboveground carbon content, which is consistent with previous studies [36,37].…”
Section: Discussionsupporting
confidence: 89%
“…Given its dominance, red maple's lower leaf dark respiration rate could explain why ecosystem respiration declined even though soil respiration, overwhelmingly the largest source of respiratory CO 2 , did not differ between control and treatment forests. Rather than increasing NEP by enhancing canopy complexity as we hypothesized, the mortality of slowly growing aspen and birch appears to have competitively "released" more vigorous mid-latesuccessional species, akin to a moderate canopy thinning that enhances access to growth-limiting resources (Campbell et al 2009, Matsushita et al 2015, Hou et al 2016.…”
Section: Confronting the Core Forest Accelerated Succession Experiments Hypothesis With Observationsmentioning
confidence: 90%
“…It is because the studied trees are still young and thinning facilitates growing of the individual trees. Thinning promotes growth of the remaining individual trees by reducing competition and increasing light and nutrient availability 29 . In contrast, thinning still results in some reduction of carbon stock so it takes a period of time to recover.…”
Section: Discussionmentioning
confidence: 99%